Vitamin D (1, 25(OH)2D3) induces α-1-antitrypsin synthesis by CD4+ T cells, which is required for 1, 25(OH)2D3-driven IL-10. Issue 189 (May 2019) - Dimeloe, Sarah; Rice, Louise V.; Chen, Hebe; Cheadle, Charlotte; Raynes, John; Pfeffer, Paul; Lavender, Paul; Richards, David F.; Nyon, Mun Peak; McDonnell, James M.; Kemper, Claudia; Gooptu, Bibek; et al.
Highlights: Human CD4 + T cells exposed to 1, 25(OH)2 D3 secrete α-1-antitrypsin – representing a novel cellular source of this protein. α-1-Antitrypsin promotes IL-10 secretion by human CD4 + T cells, via direct interaction with complement C3a. 1, 25(OH)2 D3 is unable to increase IL10 transcription in CD4 + T cells from α-1-antitrypsin-deficient individuals. Therefore, autocrine α-1-Antitrypsin is required for 1, 25(OH)2 D3-driven IL-10 expression. Abstract: Studies to identify novel immune-regulatory functions of active vitamin D (1, 25(OH)2 D3) in human CD4 + T cells revealed that 1, 25(OH)2 D3 potently induced expression of the gene SERPINA1, encoding the anti-protease α-1-antitrypsin. We confirmed α-1-antitrypsin protein expression by 1, 25(OH)2 D3-treated CD4 + T cells, but not in CD8 + T cells or monocytes. α-1-Antitrypsin promotes anti-inflammatory IL-10 synthesis in other immune cell populations. We therefore investigated its immune-regulatory effects in CD4 + T cells. Plasma-derived α-1-antitrypsin drove IL-10 synthesis by CD4 + T cells, which was not dependent on anti-protease activity, but appeared to require a serum-binding factor, since this could not be achieved with recombinant protein. α-1-Antitrypsin is reported to bind complement components, which regulate T cell function. A role for this interaction was therefore probed. Plasma-derived, but not recombinant α-1-antitrypsin contained C3a. Surface Plasmon Resonance and Microscale Thermophoresis demonstrated α-1-antitrypsin binding to C3a. Addition of C3a to CD4 + T cells cultured with recombinant α-1-antitrypsin restored induction of IL-10, whereas neutralisation of C3a abrogated IL-10 induced by plasma-derived α-1-antitrypsin. To interrogate an endogenous role for the α-1-antitrypsin-C3a axis in 1, 25(OH)2 D3-driven CD4 + T cell IL-10 synthesis, we treated cells from healthy or α-1-antitrypsin-deficient individuals (which transcribe SERPINA1 but do not secrete protein) with 1, 25(OH)2 D3. A significant correlation was identified between SERPINA1 and IL10 gene expression in healthy donor CD4 + T cells, which was absent in cells from α-1-antitrypsin-deficient individuals. Therefore, α-1-antitrypsin is required for 1, 25(OH)2 D3-induced IL-10 expression in CD4 + T cells, interacting with C3a to drive IL-10 expression.